Impact of organic fertilizers on the quality of mango var. ‘Kent’ during physiological and commercial maturity - Morocho Romero, Henry Hoseph (2026)
Mango (Mangifera indica L.) is a key fruit crop in Peru; however, its reliance on chemical fertilizers raises concerns regarding fruit quality and environmental sustainability. This study evaluated the effects of soil-applied compost and foliar-applied biol on the quality of 'Kent' mango fruits at physiological and commercial maturity stages. Conducted during the 2022–2023 season, the experiment used a 3 × 3 factorial design with compost applied at 0, 5, and 15 t/ha and biol at 0, 5, and 10%, plus a chemically fertilized control. Results revealed significant compost–biol interactions. At physiological maturity, treatments 5-10, 15-5 and 15-10 improved pulp color, soluble solids, titratable acidity, and dry matter content, achieving a desirable yellow pulp (2.0 on the scale), 9.29 °Brix, 1.23% acidity, and 20.96% dry matter—surpassing the control. At commercial maturity, these treatments also enhanced fruit firmness (0.42 MPa), reduced acidity (0.47%), increased pulp pH (4.69), and intensified orange pulp color. Overall, organic fertilization, particularly higher compost and biol doses, significantly improved fruit quality parameters compared to conventional chemical management. These findings highlight the potential of integrating organic amendments to promote sustainable mango cultivation while maintaining or enhancing fruit quality, thus providing a viable alternative for eco-friendly nutrient management in mango orchards.